Application of Mammalian Nudix Enzymes to Capped RNA Analysis - Maciej Lukaszewicz (MDPI AG, 2024)
Following the success of mRNA vaccines against COVID-19, mRNA-based therapeutics have now become a great interest and potential. The development of this approach has been preceded by studies of modifications found on mRNA ribonucleotides that influence the stability, translation and immunogenicity of this molecule. The 5' cap of eukaryotic mRNA plays a critical role in these cellular functions and is thus the focus of intensive chemical modifications to affect the biological properties of in vitro-prepared mRNA. Enzymatic removal of the 5' cap affects the stability of mRNA in vivo. The NUDIX hydrolase Dcp2 was identified as the first eukaryotic decapping enzyme and is routinely used to analyse the synthetic cap at the 5' end of RNA. Here we highlight three additional NUDIX enzymes with known decapping activity, namely Nudt2, Nudt12 and Nudt16. These enzymes possess a different and some overlapping activity towards numerous 5' RNA cap structures, including non-canonical and chemically modified ones. Therefore, they appear as potent tools for comprehensive in vitro characterisation of capped RNA transcripts, with special focus on synthetic RNAs with therapeutic activity.